Studies on the Biology of Groundnut Bruchid, C. serratus on Stored Groundnut - Oaya, C. S.; Malgwi, A. M. (Horticultural Biotechnology Research, 2018)
Studies on the biology of groundnut bruchid, Caryedon serratus Olivier was done in the present work. The study considered the pre-oviposition stage, incubation stage, larval stage, pupal stage, adult stage and the total life cycle of the bruchid (male and female). The experiment was carried out under Laboratory conditions at 30-350C temperature and 70-90% relative humidity. After the experiment was established, weekly counting of the total number of eggs laid was carried out at intervals. The results showed that, the mean developmental stages in both female and male bruchids were: 6.50 and 6.00; 17.00 and 18.00; 13.50 and 13.50; 12.00 and 13.50; 48.00 and 50.00 for incubation stage, larval stage, pupal stage, adult stage and total life cycle of the bruchids respectively. Moreover, the mean pre-oviposition and oviposition stages in female adult bruchid were: 1.50 and 5.50 respectively.